PELAKSANAAN PEMANFAATAN MEDIA BARANG BEKAS DALAM KEGIATAN PENGABDIAN MASYARAKAT DI DESA SUMBER PADI DSN V - Nasution, Raisah Armayanti; Hasri, Adinda; Dwi Ramzani, Ovy; Torfi Rangkuti, Ihsania (Al Fitrah: Journal Of Early Childhood Islamic Education, 2025)
This community service activity was driven by the belief that developing motor skills in early childhood is important, and that creative, environmentally friendly play can help. The goal of this activity was to help children improve their fine and gross motor skills using reusable, everyday materials. The activity took place in the backyard of a house in Sumber Padi Village and involved children aged 4 to 8 years old. The materials used were a cardboard bookshelf, a flower vase made from a plastic bottle, a flannel clock, and a cardboard owl decoration. To collect data, we used participant observation and recorded the activity process. We analyzed the results descriptively. The results showed that playing with reusable materials helps children improve their motor skills, encourages creativity, and helps them learn about environmental stewardship from an early age.